Horizontal plane course-stability and manoeuvres of a twin-screw surface combatant depending on appendage dimensions - Dong-Jin Kim; Haeseong Ahn; Dong Jin Yeo (International Journal of Naval Architecture and Ocean Engineering)
In this study, powering and manoeuvring performance of a twin-screw surface combatant, ONR tumblehome (ONRT), are estimated through towing tank captive model tests, and influences of appendage dimensions on its course-stabilities and manoeuvres are investigated by system-based simulation techniques. At first, resistance and propulsion tests are carried out at Froude numbers up to 0.4 in the towing tank of Korea Research Institute of Ships and Ocean Engineering (KRISO) so that its full-scale powering performance can be considered in the present simulation model. In particular, the residuary resistance is significantly affected by patterns of hull generated waves. Secondly, horizontal planar motion mechanism (HPMM) tests are performed to derive hydrodynamic coefficients in surge, sway, and yaw directions. By using 3-DoF modular-type models, turn and zig-zag manoeuvres are simulated, and simulations are validated with existing benchmark free-run model tests. Sway-yaw coupled linear whole ship models are also established in order to assess a straight-line stability of a rudder-fixed ONRT whole ship. Linear hydrodynamic coefficients are decomposed into hull and appendage components so that influences of appendage dimensions on ship manoeuvres can be analyzed in more detail. When the rudder area is enlarged or reduced, the coefficient and the location of a centerline skeg are redesigned under the constraint straight-line stabilities are identical. For one original ONRT and two modified ships, turn and zig-zag manoeuvres are simulated by linear whole ship models. Even though straight-line stabilities are identical, the turning diameter is decreased while zig-zag overshoot angles are increased with increasing rudder area. To ensure sufficient manoeuvrabilities of such a twin-screw ship, careful attentions should be paid to design of a centerline skeg and rudders.